Evaluating the Reporting Quality of Researcher-Developed Alphabet Knowledge Measures: How Transparent and Replicable Is It? - Horner, Sherri L.; Shaffer, Sharon A. (Frontiers in Psychology, 2021)
The American Educational Research Association and American Psychological Association published standards for reporting on research. The transparency of reporting measures and data collection is paramount for interpretability and replicability of research. We analyzed 57 articles that assessed alphabet knowledge (AK) using researcher-developed measures. The quality of reporting on different elements of AK measures and data collection was not related to the journal type nor to the impact factor or rank of the journal but rather seemed to depend on the individual author, reviewers, and journal editor. We propose various topics related to effective reporting of measures and data collection methods that we encourage the early childhood and literacy communities to discuss.